Myco-metabolites as biological control agents against the two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae) - Mohamed E. Osman; Amany A. Abo Elnasr; Mohamed A. Nawar; Gohyza A. Hefnawy (Egyptian Journal of Biological Pest Control, 2019)
Abstract Fungi are a promising source for bioactive secondary metabolites against various agricultural pests. Soil samples were collected from the rhizosphere of various plants at El-Khatatba, Egypt, in May 2016. Sixty-two fungal isolates were locally isolated and screened against Tetranychus urticae Koch (Acari: Tetranychidae). Four fungal strains, showed potent control activities, were morphologically identified. Laboratory evaluation of the crude extracts of the selected strains, Aspergillus melleus, A. terreus, Emericella nidulans, and Chaetomium globosum, exhibited LC50 values of 10.27, 33.05, 14.68, and 22.40 mg/ml against females of T. urticae, respectively. Correspondent LC50 values that exhibited on eggs were 8.81, 23.17, 11.66, and 11.05 mg/ml. Consequently, secondary metabolites of A. melleus were separated by liquid chromatography/mass spectrometry. Compounds separated from the active fraction were identified as mellamide, ochratoxin C, nodulisporic acid, 7-Oxocurvularin, and 6-(4′-hydroxy-2′-methyl phenoxy)-(−)-(3R)-mellein. Obtained secondary metabolites are promising sources for biopesticides to be used in bio-rationale control of T. urticae.